The importance of opportunity recognition behaviour and motivators of employees when engaged in corporate entrepreneurship - Urban, Boris; Wood, Eric (Journal of Business Economics and Management, 2015)
Organisational innovation depends on individuals and managers fostering and maintaining the innovative capacities of the firm, where opportunity recognition is important for promoting corporate entrepreneurship. The study is unique in its focus on understanding opportunity recognition behaviours and motivators of employees and how these perceptions may influence corporate entrepreneurial activity. The study is conducted in an under-researched emerging market context, where 187 respondents were surveyed in the financial sector industry. The empirical findings indicate that employees perceive themselves as having high levels of opportunity recognition behaviours and motivators which are positively associated with willingness to engage in corporate entrepreneurial initiatives. The results further show that there is a significant positive relationship between opportunity recognition behaviours and the frequency of opportunities recognised. Implications highlight the importance of fostering opportunity recognition behaviours within an organisation and motivating employees to act innovatively.